2014
DOI: 10.1007/s11434-013-0069-5
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and risk factors of hand, foot, and mouth disease in Changchun, northeastern China

Abstract: Hand, foot, and mouth disease (HFMD) is a public health problem, and there have been increasing numbers of outbreaks in mainland China since 2008. Over 17,000 HFMD cases have been reported in Changchun between 2008 and 2011. This study characterized the temporal and spatial distribution of the disease and identified the risk factors for HFMD. The main findings were as follows: (i) there were significant differences in HFMD incidence among age groups, with 86.8 % of reported cases in children younger than 5 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Some studies indicated that it was closely correlated to socio-economic variables: demographics, local geographic environment, socio-economic status, health conditions, and infrastructure. For example, Yan et al showed that HFMD incidence was higher in urban areas compared with rural areas and demonstrated that the distance to the nearest freeway and per capital GDP are risk factors associated with HFMD incidence [ 24 ]. Hu et al indicated that the population density of children can explain 56% of the variance in the cumulative monthly HFMD incidences in 2912 counties in China [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies indicated that it was closely correlated to socio-economic variables: demographics, local geographic environment, socio-economic status, health conditions, and infrastructure. For example, Yan et al showed that HFMD incidence was higher in urban areas compared with rural areas and demonstrated that the distance to the nearest freeway and per capital GDP are risk factors associated with HFMD incidence [ 24 ]. Hu et al indicated that the population density of children can explain 56% of the variance in the cumulative monthly HFMD incidences in 2912 counties in China [ 23 ].…”
Section: Introductionmentioning
confidence: 99%